Functional Thin Films and Nanostructures for Sensors Synthesis, Physics and Applications - Zribi, Anis; Fortin, Jeffrey (Integrated Analytical Systems,, 2009)
Thin films and nanostructures can play multiple roles in a sensor including structural support, reliability enhancement, filtering and transduction. These micro and nano structured materials are discussed here in the context of transduction and how they contribute to the current sensor revolution. This book covers an account of general sensors theory, design considerations, and specific case studies of functional thin films and nanostructure applications in sensing as it demonstrates the whole design process. The book is also intended to provide the more experienced designers with a condensed summary of sensor design methodology and excellent references that will prove useful in future sensor design endeavors. This book is also of interest to those with a deep knowledge of such areas of science and engineering as materials science, physics, chemistry, biology, mechanical and electrical engineering.